Analisis Korelasi : Hubungan Pengangguran terhadap Perkembangan Tingkat Kemiskinan di Kota Jambi - Nayla Desviona; Ermaini Ermaini; Mustika Mustika; Helmina Helmina; Kayla Risma Marfisya; Aulia Septia Ningrum (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the relationship between the open poverty rate (TPT) and the poverty rate in Jambi City from 2014 to 2023. Poverty and poverty are important issues in regional development because they directly impact community welfare. This study employed a quantitative method with a descriptive correlational approach, and data analysis was conducted using the Pearson correlation test. Secondary data were obtained from the Jambi City Central Statistics Agency (BPS). The results of the normality test indicated that the data were normally distributed, making them suitable for analysis using Pearson. The correlation analysis showed a correlation coefficient between the TPT and poverty of 0.049 with a significance level of 0.893, indicating no significant relationship between the two variables. This finding suggests that poverty is not the sole factor determining the poverty rate in Jambi City. Therefore, poverty alleviation requires a multidimensional approach that focuses not only on employment but also includes education, distribution of social assistance, and equitable regional development.